This generation : dispatches from China's most popular literary star (and race car driver) - Han, Han, 1982- (Simon & Schuster, 2012)
"For those who follow Chinese affairs, Han Han is as controversial as they come-an irreverent singer, sports celebrity, and satirist whose brilliant blogs and books have made him a huge celebrity with more than half a billion readers. Now, with this collection of his essays, Americans can appreciate the range of this rising literary star and get a fascinating trip through Chinese culture."--Dust jacket.